An anisotropic localizing gradient damage approach for failure analysis of fiber reinforced composites. (15th August 2022) - Negi, Alok; Soni, Aakash; Kumar, Sachin
Abstract: This article presents an anisotropic gradient-enhanced continuum damage model developed within the finite element method framework to address complex fracture phenomena in anisotropic layered materials with unidirectional fiber-reinforced composites as the primary material examples. The main objective of the work is to model damage anisotropy due to progressive intra-laminar fracture at mesoscale in transversally isotropic composite laminae using distinct damage variables associated with different in-plane failure modes. Departing from the conventional gradient enhancements, the model adopts an improved spatial nonlocal description to ensure correct localized damage bandwidths using a single internal length scale. The coupled system of equations is decoupled using an operator-split (staggered) methodology to ensure a robust and straightforward computational implementation without compromising accuracy using lower order finite elements. The proposed damage model is tested on experimental results of fracture response in a single-edge notched tension, center notched tension, and open-hole tension fiber-reinforced composite laminae, where the numerical results were consistent with experimental observations.